1984
DOI: 10.1111/j.1752-1688.1984.tb04676.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Rising Irrigation Costs in the Great Plains1

Abstract: Irrigation costs are rising rapidly on the 32 million acres irrigated with ground water. Ground water levels are declining under about 15 million of those acres adding to increased costs. However, from 1975 to 1982, 75 to 80 percent of increased ground water irrigation costs were due to higher nominal energy prices and interest rates. In real dollars, adjusted for inflation, these costs have risen faster than other irrigation costs and the real rise in commodity prices has been very small. A continuation of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In a similar vein we assume a fixed energy mix and constant (real) energy costs. See Sloggett and Mapp [1984] for a discussion of the implications of rising energy prices.…”
Section: Overview Of the Model And Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein we assume a fixed energy mix and constant (real) energy costs. See Sloggett and Mapp [1984] for a discussion of the implications of rising energy prices.…”
Section: Overview Of the Model And Related Literaturementioning
confidence: 99%
“…where SL is the surface level above the reference plane, so To formalize this, following Sloggett and Mapp [1984], well yield in acre-feet per hour is given by…”
Section: C(h W) = Bl(sl -H(t))w(t)mentioning
confidence: 99%
“…The Ogallala is largely a fossil aquifer with a very slow rate of natural recharge. By 1977, groundwater levels were declining by at least 15 cm per year in 82% of the area irrigated with groundwater in Texas (Sloggett and Mapp, 1984). Severe overdraft was observed also in Kansas, Oklahoma, and New Mexico.…”
Section: Irrigating With Groundwater On the High Plainsmentioning
confidence: 99%
“…Concurrently, there has been a dramatic increase in the cost of energy for pumping since 1973. Energy has become one of the more important factors in irrigated crop production (Sloggett and Mapp, 1984). A 1975 study showed that 53 percent of the total variable costs of producing corn in the Great Plains was energy related (Skold, 1977).…”
Section: Introductionmentioning
confidence: 99%